2017
DOI: 10.1037/xge0000343
|View full text |Cite
|
Sign up to set email alerts
|

The devil’s in the detail: Accessibility of specific personal memories supports rose-tinted self-generalizations in mental health and toxic self-generalizations in clinical depression.

Abstract: Models of memory propose that separate systems underpin the storage and recollection of specific events from our past (e.g., the first day at school), and of the generic structure of our experiences (e.g., how lonely I am), and that interplay between these systems serves to optimize everyday cognition. Specifically, it is proposed that memories of discrete events help define the circumstances (boundary conditions) in which our generalized knowledge applies, thereby enhancing accuracy of memory-dependent cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 69 publications
2
38
0
Order By: Relevance
“…We further identify a potential cognitive mechanism whereby specific positive memories predict lower negative self-cognitions in response to stress. As such, it may be that specific positive memories help form boundaries to the scope of negative self-cognitions, thereby reducing the likelihood of the emergence of depressogenic symptoms 36 . We recently showed that emphasising the value of positive social experiences as part of a brief psychological treatment programme can lead to depressive symptom reduction on par with existing treatments in depressed adolescents 37 .…”
Section: Insert Table About Herementioning
confidence: 99%
“…We further identify a potential cognitive mechanism whereby specific positive memories predict lower negative self-cognitions in response to stress. As such, it may be that specific positive memories help form boundaries to the scope of negative self-cognitions, thereby reducing the likelihood of the emergence of depressogenic symptoms 36 . We recently showed that emphasising the value of positive social experiences as part of a brief psychological treatment programme can lead to depressive symptom reduction on par with existing treatments in depressed adolescents 37 .…”
Section: Insert Table About Herementioning
confidence: 99%
“…The generalized summaries provided by categoric memories guide efficient decision making (Klein et al, 2001;Cosmides & Tooby, 2000), while specific memories play an important role in problem solving (Jing et al, 2016) and facilitating social interaction (Beike et al, 2016)everyday skills which are compromised during depression, subsequently driving functional impairment. Further, we recently demonstrated that interaction between generalisations and specific memories may serve to shape emotionally valenced selfevaluations (Hitchcock, Rees, & Dalgleish, 2017). Improving the ease with which depressed individuals can generate these different memory types on demand, and move between them, may therefore help to alleviate symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%
“…cognitively reappraise difficult situations, solve problems, and populate the details of future plans by providing detailed information about what has worked in the past ( Jing et al, 2016) and set boundary conditions for the validity of generalized memories (Hitchcock, Rees, & Dalgleish, 2017).…”
mentioning
confidence: 99%